Search Club: Using peer support to develop search skills and share knowledge in a specialist NHS team. (1st October 2021) - Nicholas, Katie; Hopkins, Emily; Jordan, Liz; McCrossan, Jo; Hunt, Matt; Greenfield, Katy
Abstract: The newly‐formed Knowledge Management team at Health Education England (HEE) established an internal "Search Club" for their Knowledge Specialists to share good practice, exchange ideas, and discuss approaches to developing search strategies. The article describes how this was initiated and run online. The sessions improved the Knowledge Management team skills, and gave them an opportunity to share and learn from each other. A further benefit has been the creation of resources such as a "synonyms bank", search strategies, and a bank of grey literature sources. These reduce duplication of effort, save time, and improve consistency across the team's output. D.I.